Analysis of the epidemiological profile of Hepatitis B cases in the metropolitan region of São Paulo from 2010 to 2020 - Bocchi , Letícia Ribeiro; Freitas, Lívia Nogueira de (Seven Editora, 2024)
This study evaluates the epidemiological profile of patients with Hepatitis B in the Metropolitan Region of São Paulo (MRSP), notified between 2010 and 2020. Secondary data were collected through the Notifiable Diseases Information System of the Ministry of Health (SINAN) and analyzed through a descriptive cross-sectional study. The determinants used to study the prevalence of the disease were gender, age group, race, and area of residence. A total of 1,384 cases were reported, with a predominance of cases in males (71.96%; n=996), aged 20 to 39 years (52.67%; n=729), self-declared white race (45.66%; n=632), with the city of São Paulo being the region with the highest prevalence of the disease (74.20%; n=1,027). The evaluation of the variables schooling and mechanism of infection were impaired due to incomplete completion or non-completion of the field in the notification forms. The present study aims to identify high-risk groups, outlining etiological hypotheses for prevention purposes and future investigations. DOI:https://doi.org/10.56238/sevened2024.001-019